Genomics, public health and identity - Chadwick, Ruth (Acta Bioethica, 2003)
This paper questions the utility of the ethical principles that are usually invoked to deal with genomic issues, particularly genetic databases. Concepts such as solidarity, benefit sharing, equity, public participation, and collective identity are discussed. The author argues that genetic banks are precipitating new concern over group interest, as opposed to concern over issues arising from individualistic medical ethics. Genomics era needs new paradigms in ethics. An individualistic approach based on choice and autonomy is not useful, because we make choices not only as individuals but also as members of different groups. The doctrine of informed consent evolved in different historical conditions from the ones we face in the era of genomics. This is complicated by the global context of genetic research, in addition to powerful commercial interests. This suggests that it is not sufficient to move from an individual-centred ethic approach to a more community-centred one; an approach of renegotiating the relationship between individual and community. We need also to be clear about what the interests at stake are, which may mean reconceiving the terms ‘individual' and ‘community' in this context and the ways in which their interests are affected, identifying the sources of collective identity that are at stake